Marine Stratocumulus Clouds With More Coarse Sea Spray Aerosols Are Brighter - Fan Liu; Feiyue Mao; Daniel Rosenfeld; Zengxin Pan; Lin Zang; Yannian Zhu; Wei Gong (Geophysical Research Letters)
Abstract The idea of cooling the Earth by marine cloud brightening is well established. All prior studies considered enhancing cloud albedo only with fine aerosols (FA). Adding coarse sea spray aerosols (CSA, radius>1 μm) has been thought to have the opposite effect. Using nearly a decade of satellite observations and global aerosol reanalysis, we found that the maximum radiative cooling effect from marine stratocumulus occurs when FA is around 3 μg m−3 and CSA is around 30 μg m−3. Under low winds and high stability conditions, optimal FA and CSA can enhance cooling by −95 W m−2, nearly 60% more than adding FA alone. This CRE response to FA and CSA was consistently observed across various cloud‐controlling factors, thus minimizing the probability of being caused by meteorological co‐variability. These findings improve our understanding of how different aerosols affect Earth's climate, improve the evaluation of cooling achieved through marine cloud brightening, and support its feasibility.